Fixed Point Theorems for Pemetaan Nonexpansive, Nonspreading, and Hybrid Mappings in Hilbert Space - Firman Riansyah (International Journal of Transdisciplinary Knowledge, 2021)
A Firmly nonexpansive mapping is a map which is closely related to equilibrium problems. Nonexpansive, nonspreading, and hybrid mappings are nonlinear mappings in Hilbert spaces. In this paper, we show the existence of a fixed point of nonexpansive, nonspreading, and hybrid mappings in Hilbert space using Banach limit.